2015
DOI: 10.4314/gjds.v12i1-2.2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-efficacy Beliefs: The Relationship between Gender and Instructional Strategies, Classroom Management and Student Engagement

Abstract: The study investigated the relationship between gender and self-efficacy beliefs in instructional strategies, classroom management and student engagement among senior high school teachers in Kumasi metropolis, as most previous studies tend to focused on the developed countries other than developing countries like Ghana. Specifically, descriptive survey design was used to determine the levels of self-efficacy beliefs among the teachers and the relationship between gender and teachers' self-efficacies were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
5
24
1
3
Order By: Relevance
“…Their conclusion was that gender differences did exist in two of the domains whereas Butucha (2013), in his study of Ethiopian teachers by gender, found significant differences between males and females in all domains. Similar results are also reported by others like Sarfo, Amankwah, Sam & Konin (2015) and Butucha (2014). These research studies re-confirm the differences between the self efficacy of males and females in various contexts.…”
Section: Self Efficacy and Gendersupporting
confidence: 91%
“…Their conclusion was that gender differences did exist in two of the domains whereas Butucha (2013), in his study of Ethiopian teachers by gender, found significant differences between males and females in all domains. Similar results are also reported by others like Sarfo, Amankwah, Sam & Konin (2015) and Butucha (2014). These research studies re-confirm the differences between the self efficacy of males and females in various contexts.…”
Section: Self Efficacy and Gendersupporting
confidence: 91%
“…In addition, another variable that does not predict the classroom management competence level of faculty of education students is gender. When the literature is reviewed, there are both researches which indicate that the classroom management perception of teachers and faculty of education students differs significantly according to the gender variable (Andersen, 2011;Chudgar & Sankar, 2008;Demirtaş, Cömert & Özer, 2011;Erden, Aytaç & Erden, 2016;Khan, Khan & Majoka, 2011;Martin, Yin & Mayall, 2006;Sarfo, Amankwah, Sam & Konin, 2015;Yeşilyurt, 2013) and researches which indicate that there is not a significant difference between them (Kahyaoğlu &Yangın, 2007;Taşkaya & Uyar, 2017;Shoulders & Krei, 2015;Uslu & Avcı, 2016;Yılmaz & Aydın, 2015).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Studies conducted on the association between self-efficacy beliefs and learner engagement reveal that self-efficacy beliefs and student engagement are crucial factors for effective teaching (Beri & Stanikzai, 2018;Kazempour & Sadler, 2015). In educational settings, teacher self-efficacy is conceptualised as the teacher's beliefs in their ability to plan, organise and implement effective instructional practices in a lesson (Kazempour & Sadler, 2015;Sarfo et al, 2015). Bandura (1995) postulated that teachers who perceive a task as difficult are likely to abandon it, and vice versa, implying that the self-efficacy of a teacher can impact their ability to appropriately implement instructional practices.…”
Section: Development Of Self-efficacy In Teacher Learningmentioning
confidence: 99%